Dietary Supplementation With Bacillus subtilis Promotes Growth and Gut Health of Weaned Piglets - Tian, Zhilong; Wang, Xiaodan; Duan, Yehui; Zhao, Yue; Zhang, Wenming; Azad, Md. Abul Kalam; Wang, Zhanbin; Blachier, Francois; Kong, Xiangfeng (Frontiers in Veterinary Science, 2021)
This study was conducted to investigate the effects of dietary supplementation with different types of Bacillus subtilis (B. subtilis) on the growth and gut health of weaned piglets. A total of 160 piglets were randomly assigned into four groups: control group (a basal diet), BS-A group (a basal diet supplemented with B. subtilis A at 1 × 106 CFU/g feed), BS-B group (a basal diet supplemented with B. subtilis B at 1 × 106 CFU/g feed), and BS-C group (a basal diet supplemented with B. subtilis C at 1 × 106 CFU/g feed). All groups had five replicates with eight piglets per replicate. On days 7, 21, and 42 of the trial, blood plasma and intestinal tissues and digesta samples were collected to determine plasma cytokine concentrations, intestinal morphology, gut microbiota community and metabolic activity, and the expression of genes related to gut physiology and metabolism. The results showed that dietary B. subtilis supplementation improved (P < 0.05) the body weight and average daily gain (in BS-B and BS-C groups) of weaned piglets and decreased (P < 0.05) the diarrhea rates (in BS-A, BS-B, and BS-C groups). In the intestinal morphology analysis, B. subtilis supplementation improved (P < 0.05) the size of villus height and villus height to crypt depth ratio in the ileum of weaned piglets. Firmicutes, Bacteroidetes, and Tenericutes were the most dominant microflora in piglets' colon whatever the trial group and time of analysis. Dietary BS-C supplementation increased (P < 0.05) the relative abundances of Anaerovibrio and Bulleidia and decreased (P < 0.05) the relative abundances of Clostridium and Coprococcus compared with the control group. In addition, dietary B. subtilis supplementation increased (P < 0.05) the indicators of intestinal health, including plasma levels of interleukin (IL)-2 and IL-10, as well as the colonic levels of short-chain fatty acids. Furthermore, dietary B. subtilis supplementation also up-regulated (P < 0.05) the expression of genes involved in metabolic pathways related to intestinal microbiota maturation. In conclusion, these findings suggest that a diet containing BS-B or BS-C can efficiently promote growth performance, decrease diarrhea incidence, and ameliorate several indicators of intestinal health through the modulation of gut microbiota composition and metabolic activity in weaned piglets.